Privatisierung in der deutschen Rechtsordnung - Kirchner, Christian (Zeitschrift für Japanisches Recht, 2006)
The discussion regarding privatization marks a new determination of the state and its tasks. In Germany as well as in other countries, this discussion has not yet been concluded. From a legal point of view, privatization is the transition from a state which undertakes to supply its citizens with public services to a state which confines itself to its responsibility for merely guaranteeing such services. European law also plays a major role: The obligation to create the single market requires that isolated national markets for public services be opened up; that is to say, the state has to withdraw from monopolistic economic activity and make way for private competition. In the case of network industries, the state has the task of guaranteeing infrastructure and ensuring that basic needs are provided for. Privatizations in network sectors where network monopolies exist also entail regulation. By means of sector-specific regulations or the general competition and anti-trust law provisions, competition is ensured even if there are monopolistic structures. The discussion regarding privatization has several layers. It is determined by economic as well as political factors and by European law. The fundamental policy question concerns the new role of the state guaranteeing services, but also of the state which sets the rules for the newly developing competition by means of competition and anti-trust law. The article deals with the various aspects of privatization in German law by establishing fourteen theses. (The Editors)